Participatory Design Public Policy Networks for Addressing School Dropout Rates within the Framework of Ecuador´s Ten-Year Education Plan 2006-2016 - Castellanos Vela, Diana (2020)
This document analyzes the participation of a network of stakeholders established to design public policies which address the school dropout phenomenon within the frameworks of arising from Ecuador´s Ten-Year Education Plan (PDE) 2006-2016. This study was conducted after the PDE was ratified in a public consultation process, which marked a milestone in the participatory design of public education policies. The study probes at the stakeholder network based on the neoinstitutional sociological theory of public policy analysis to identify which stakeholders are linked to the public arena and how they group together to exchange resources and position themselves. Given that many stakeholders that contribute to the development of educational policies, this study uses the Ideational Model proposed by Kisby (2007) to identify stakeholders, describe the context and decide the participatory process for policy outcomes.  Based on this model and the stakeholder network methodology, one can determine if the PDE included a participatory process to address the school dropout phenomenon and if these networks were participatory, heterogenous and produced innovated results, such as the three aforementioned variables which serve as the focus of this study (Sandström y Carlsson, 2008).